ЖАМИЯТ ҲАЁТИГА МАФКУРАВИЙ МУНОСАБАТЛАРНИНГ ТАЪСИРИ ВА УЛАРНИНГ НАМОЁН БЎЛИШ ХУСУСИЯТЛАРИ (Scientific journal of the Fergana State University, 2023)
This article illustrates the  peculiarities of the influence of essense and content  as well as the significance of idealogical processes  and  relations to the development of society